2021
DOI: 10.3390/foods10081681
|View full text |Cite
|
Sign up to set email alerts
|

Total and Partial Fat Replacement by Gelled Emulsion (Hemp Oil and Buckwheat Flour) and Its Impact on the Chemical, Technological and Sensory Properties of Frankfurters

Abstract: A gelled emulsion (GE) prepared with hemp oil and buckwheat flour was used to replace pork back fat in frankfurters. Five different formulations were prepared: control (with 35% pork back fat—SC), and the following four to achieve 25%, 50%, 75%, and 100% pork back fat substitution by GE (S1, S2, S3, and S4, respectively). Nutritional, technological, and sensorial characteristics of frankfurters were evaluated. Sausages containing GE presented a lower total fat content with a higher amount of polyunsaturated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…The ash content between treatment was not significantly different (P>0.05) due to the low mineral content of each fat replacer and meat analogue ingredients. These result in accordance with Martinez et al [11] which explained that there was no significant difference in the ash content of frankfurters using a fat replacer from hemp oil and wheat flour.…”
Section: Ash Contentsupporting
confidence: 92%
“…The ash content between treatment was not significantly different (P>0.05) due to the low mineral content of each fat replacer and meat analogue ingredients. These result in accordance with Martinez et al [11] which explained that there was no significant difference in the ash content of frankfurters using a fat replacer from hemp oil and wheat flour.…”
Section: Ash Contentsupporting
confidence: 92%
“…The diameter reduction was calculated according to Equation (7); the thickness increase was calculated according to Equation (8); and to estimate the cooking loss, Equation ( 9) was performed: The extraction of the (poly)phenolic and methylxanthine compounds from the beef burgers was divided into two fractions: (i) extracts with the free (poly)phenolic compounds and (ii) extracts with bound-insoluble (poly)phenolic compounds. To obtain the free (poly)phenolic extracts, the methodology reported by Genskowsky et al [26] was used.…”
Section: Cooking Characteristics Of Beef Burgersmentioning
confidence: 99%
“…Among all of these strategies, the use of gelled emulsions has great potential for their use as a fat substitute in meat products. Therefore, several scientific studies have demonstrated the high potential of this type of structured oils as fat replacers [7][8][9][10]. To elaborate, several components of a gelled emulsion could be used; however, oils that show emulsifying and gelling properties are the ones that could be adapted the best for the development of these matrices.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our results were consistent with those obtained in previous studies [3] , [7] , [9] . There were two possible explanations for this phenomenon: i) The oil droplets in the gel matrix were attributed to a light-scattering effect, with the increase in oil content accompanied by more light reflectance, resulting in the improvement of the color parameters [2] , and ii) the emulsion formed in the water–protein–oil system caused the light-scattering effect in the gels, leading to an increase in whiteness [34] . Overall, the incorporation of edible oil presents an effective and direct method for generating emulsified gel products with superior whiteness.…”
Section: Resultsmentioning
confidence: 99%